If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2h = 3b Reorder the terms: -2h + x = 3b Solving -2h + x = 3b Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1x' to each side of the equation. -2h + x + -1x = 3b + -1x Combine like terms: x + -1x = 0 -2h + 0 = 3b + -1x -2h = 3b + -1x Divide each side by '-2'. h = -1.5b + 0.5x Simplifying h = -1.5b + 0.5x
| 3x-4y-24=0 | | m=5y+6x | | 4x+64=9x-11 | | 5p^2-49p-10=0 | | (y-5)=4y | | x/8=229 | | -2y+16=32 | | -3(2t+1)=-9 | | (1/2)lg | | 2(f-1)=-2 | | 1.3r-0.7=12 | | -10(s+2)=-75 | | n/2-5=6 | | 8a+3b=28 | | 43+5+b=52 | | x+4y=4.3 | | a/b-5=12 | | 6+55x=33x+2 | | 3x^2+2x-11=13+12x | | 7r^2+8r=0 | | 4s^2+7-9=39 | | 8h^2+23h-3=0 | | a-3b=17 | | 9x^2+4y^2-4=0 | | 35+b+45=180 | | 7+3x=10-x | | (15x)+(10y)=210 | | 2-3b=17 | | 3u^2+4u-4=0 | | 4s^2-2=39 | | -2n+4n?2-8-12n= | | 38+b=64 |